Parental consent in paediatric clinical research. Issue 2 (24th October 2005) - Chappuy, H; Doz, F; Blanche, S; Gentet, J-C; Pons, G; Tréluyer, J-M
Abstract : Aims: To assess parental understanding and memorisation of the information given when seeking for consent to their child's participation to clinical research, and to identify the factors of significant influence on parents' decision making process. Methods: Sixty eight parents who had been approached for enrolling their child in a clinical oncology or HIV study were asked to complete an interview. Their understanding was measured by a score which included items required to obtain a valid consent according to French legislation. Results: Items that were best understood by parents were the aims of the study (75%), the risks (70%), the potential benefits to their child (83%), the potential benefits to other children (70%), the right to withdraw (73%), and voluntariness (84%). Items that were least understood were the procedures (44%), the possibility of alternative treatments (53%), and the duration of participation (39%). Less than 10% of the parents had understood all these points. Ten parents (15%) did not remember that they had signed up for a research protocol. Thirty three parents (48%) reported no difficulty in making their decision. Twenty four parents (38%) declared that they made their decision together with the investigator; 26 (41%) let the physician decide. Fifty four parents (78%) felt that the level of information given was satisfactory. Conclusion: There was an apparent discrepancy between parents' evaluation of the adequacy of the information delivered and evaluation of their understanding and memorisation. The majority of parents preferred that the physician take as much responsibility as possible in the decision making process.